2012
DOI: 10.1038/ncomms2199
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of VE-cadherin is modulated by haemodynamic forces and contributes to the regulation of vascular permeability in vivo

Abstract: Endothelial adherens junctions maintain vascular integrity. Arteries and veins differ in their permeability but whether organization and strength of their adherens junctions vary has not been demonstrated in vivo. Here we report that vascular endothelial cadherin, an endothelial specific adhesion protein located at adherens junctions, is phosphorylated in Y658 and Y685 in vivo in veins but not in arteries under resting conditions. This difference is due to shear stress-induced junctional Src activation in vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
492
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 409 publications
(523 citation statements)
references
References 61 publications
28
492
2
1
Order By: Relevance
“…Studies by Vestweber have shown that phosphorylation of the VE-cadherin tyrosine residues Y658 and Y685 regulated endothelial permeability, whereas phosphorylation of Y731 mediated leukocyte extravasation across AJs (21,26,33). Since we identified that these 3 residues were dephosphorylated by HIF2α-induced VE-PTP expression, we addressed the possibility that HIF2α is protective in models of sepsis on the basis of the dephosphorylation switch mechanism described above.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Vestweber have shown that phosphorylation of the VE-cadherin tyrosine residues Y658 and Y685 regulated endothelial permeability, whereas phosphorylation of Y731 mediated leukocyte extravasation across AJs (21,26,33). Since we identified that these 3 residues were dephosphorylated by HIF2α-induced VE-PTP expression, we addressed the possibility that HIF2α is protective in models of sepsis on the basis of the dephosphorylation switch mechanism described above.…”
Section: Discussionmentioning
confidence: 99%
“…Whichever the case is, mechanical perturbation at the VE-cadherin molecular scale may actually induce the cascade that leads to leakiness. This notion is supported by a study showing that macroscopic hydrodynamic stress on endothelial cells could bring about phosphorylation of VE-cadherin 32 .…”
Section: Discussionmentioning
confidence: 78%
“…Instead, IL-6 caused JAKdependent phosphorylation of Stat and VE-cadherin, VE-cadherin internalization, disassembly of AJs, and increased EC permeability. VE-cadherin internalization is triggered by serine/threonine or tyrosine phosphorylation mediated by p21 activated kinase (40) or Src kinase family (41,42). The JAK-dependent mechanism of IL-6-induced endothelial permeability involved downstream activation of Src, as Jak inhibitor abolished Src phosphorylation at Y-416, reflecting its activation, whereas both Jak and Src inhibitors suppressed phosphorylation of VE-cadherin ( Figure 6F) and VE-cadherin disappearance from cell junctions (data not shown).…”
Section: Discussionmentioning
confidence: 91%